Pengaruh Harga dan Kualitas Produk Terhadap Kepuasan Konsumen Pada Showroom Mobil Surya Medal Group di Kabupaten Tasikmalaya - Mohammad Dava Rifqi Hermawan; Ari Arisman; Depy Muhamad Pauzy (CV. Ulil Albab Corp, 2024)
This research aims to determine the influence of price and product quality on consumer satisfaction (Survey at the Surya Medal Group Car Showroom in Tasikmalaya Regency) simultaneously or partially. The method used in quantitative research is a consumer survey approach with 100 respondents and primary data collection in the form of a questionnaire. The analytical tool used in this research is multiple linear regression using SPSS Version 25. The research results show that price and product quality simultaneously have a significant effect on consumer satisfaction at the Surya Medal Group Car Showroom. Price partially has a significant effect on consumer satisfaction at the Surya Medal Group Car Showroom. Product quality partially has a significant effect on consumer satisfaction at the Surya Medal Group Car Showroom.